1977
DOI: 10.1210/jcem-44-3-481
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism in an Area of Endemic Goiter and Cretinism in Central Java, Indonesia

Abstract: In an area of severe endemic goiter in Central Java, Indonesia, clinical overt or mild hypothyroidism appeared to be present in 7 out of 20 cretins and also in 12 out of 94 non-cretinous subjects, all 5-20 years of age, living in the village of Sengi. Hypothyroidism was not found in a control group of 70 subjects of the same age living in Londjong just outside the edemia. In hypothyroid subjects the plasma PBI-concentration was 0.98+/-0.32 mug/100 ml (mean+/-SD) vs. 2.72+/-1.24 mug/100 ml in euthyroid subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The fact that in some children, hypothyroidism starts after the age of 3 years is consistent with the observation of Goslings et al (102) that hypothyroid patients in severe endemic goiter are not necessarily affected by severe and irreversible mental retardation and of Boyages et al (12) that cretins with thyroid failure may have only moderate retardation in height and bone maturation.…”
Section: Complicationssupporting
confidence: 87%
“…The fact that in some children, hypothyroidism starts after the age of 3 years is consistent with the observation of Goslings et al (102) that hypothyroid patients in severe endemic goiter are not necessarily affected by severe and irreversible mental retardation and of Boyages et al (12) that cretins with thyroid failure may have only moderate retardation in height and bone maturation.…”
Section: Complicationssupporting
confidence: 87%
“…The severity of the endemias was also attested by the presence of endemic cretinism with a prevalence up to 10% to 15% of the population. The historical studies performed by Djokomoeljanto and colleagues (3,(5)(6)(7)(8) indicated that in Indonesia, there was a continuous spectrum of impairment of the mental development in the whole population, of which cretinism was only the extreme form.…”
Section: Introductionmentioning
confidence: 99%
“…These differences, however, do not lead to significant differences in serum TSH levels. Since the 24 h 131I uptake is lower in the cretinous sub¬ jects, primary thyroid failure may also play a part in the reduced thyroid hormone levels in these subjects as we have described previously (Goslings et al 1977).…”
Section: Discussionmentioning
confidence: 55%
“…The community with severe iodine deficiency has already been described (Goslings et al 1975(Goslings et al , 1977 and consisted of 642 subjects living in Segni, a village situated at an altitude of 600 m in a rural area on the Western slope of the Merapi vulcano in Central Java, Indonesia. The goitre rate for the area was 85 % (classification according to Perez et al (I960)).…”
Section: Subjectsmentioning
confidence: 99%